Madagascar Public Expenditure Review 2015 : Education - World Bank Group (World Bank, Washington, DC, 2016)
Management of the primary education system in Madagascar follows a centralized model, supported by de-concentrated services. Education is divided into (a) preschool, (b) 5 years of primary education, (c) 4 years of lower secondary, (d) 3 years of upper secondary, and (e) higher education. An important feature of the Malagasy education system is the relatively well developed framework for school-based management. The school management committees (FAFs, Fiaraha-miombon’Antoka ho amin’ny Fampandrosoana ny sekoly) consist of parents, teachers, the school director, and representatives from the local community. They have been in existence in each school since 2002, when the government started providing annual grants to schools on a per capita basis to cover part of schools’ operating expenses. The FAFs are responsible for managing these grants, and play a critical role in improving accountability of service delivery and promoting community engagement and social dialogue among local stakeholders. The FAFs are also increasingly participating in the financing of school operations, including hiring and paying community teachers and financing basic supplies. Trends in contributions from school committees in the financing of education are examined in details later in the paper.